2010
DOI: 10.1177/0960327110369821
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium chloride exhibits a profound toxic effect on bacterial microflora of the mice gastrointestinal tract

Abstract: Cadmium (Cd2+), a naturally occurring heavy metal, is an important environmental pollutant and a potent toxicant to bacteria. The gastrointestinal (GI) tract microflora has a marked capacity to cope with the increased load of ingested metals. However, heavy metals may have harmful effects on GIT microflora. Under the conditions of experimental exposure to cadmium, changes in the population of intestinal microflora in healthy mice were examined. Five experimental groups received 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 45 publications
5
45
3
Order By: Relevance
“…A discriminant analysis of band classes (performed with Bionumerics software) enabled us to distinguish between fecal and colonic samples (Figure 2) and between control samples and HM-treated samples but did not pinpoint systematic differences between Pb and Cd treatments or between low and high concentrations of the HMs (results not shown). This finding contrasts with a recent report in which oral Cd had harmful effects on the viability of some components of the mouse microbiota [18]. This disparity might be explained by the fact that Fazeli and coworkers used restrictive conventional culture methods, whereas we used a molecular approach.…”
Section: Resultscontrasting
confidence: 90%
“…A discriminant analysis of band classes (performed with Bionumerics software) enabled us to distinguish between fecal and colonic samples (Figure 2) and between control samples and HM-treated samples but did not pinpoint systematic differences between Pb and Cd treatments or between low and high concentrations of the HMs (results not shown). This finding contrasts with a recent report in which oral Cd had harmful effects on the viability of some components of the mouse microbiota [18]. This disparity might be explained by the fact that Fazeli and coworkers used restrictive conventional culture methods, whereas we used a molecular approach.…”
Section: Resultscontrasting
confidence: 90%
“…93 Breton et al also reported minor but specific changes in the composition of the colonic microbiota at the family and genus levels, following chronic treatment with cadmium and lead in mice. Heavy metal-consuming animals had smaller numbers of Lachnospiraceae and larger numbers of Lactobacillaceae and Erysipelotrichaceacae than control animals.…”
Section: Environmental Chemicals Can Affect the Composition And/or Thmentioning
confidence: 96%
“…This study identified an association of Cd treatment with a decrease in mucus thickness, which supports a mechanism of increased gut permeability. Furthermore, various concentrations of heavy metals have demonstrated to be growth limiting or retarding against diverse microorganisms [20], [21]. The toxic effects of heavy metals on gut microbiota impose great impact on food digestion as well as host health [12], [13].…”
Section: Discussionmentioning
confidence: 99%